Geometry and development of Zindapir Anticlinorium, Sulaiman Range, Pakistan. (February 2020) - Jadoon, Saif-Ur-Rehman K.; Ding, Lin; Jadoon, Ishtiaq A.K.; Idrees, Muhammad; Zaib, Muhammad Owais
Abstract: Surface geological (field and Landsat images) and subsurface geophysical (seismic reflection and borehole) data were analyzed for geometry and development of N-S oriented frontal Zindapir anticlinorium in the Sulaiman Range, Pakistan. The anticlinorium with its four segments of structural relief (salients), north to south as Dhodak, Rodho, Affiband, and Zindapir, extends over about 130 km with east-vergence of the fold axis, of general NS trend, highly oblique to the plate convergence vector. Based on seismic and well data correlation, sedimentary strata are interpreted with an east to west increase in thickness over the basement, along the western passive margin of the Indian plate. The basement is modelled to have NS trend with gentle 2.5° westward dip. NS well correlation along the fold axis and seismic reflection interpretation depict structural relief of 2–4 km along different salient's. Based on seismic reflection profiles, shallow-rooted pop-ups in Tertiary and Cretaceous strata are interpreted, contrary to their earlier interpretation as thick-skinned structures. The core of the anticlinorium is occupied with duplication of Jurassic and older (Triassic) strata, of flat-ramp-flat geometry, as a fault-bend fold, and an anticlinal stack, due to variable shortening from edges to the centre (across strike) of the anticline. It is interpreted to develop along lateral ramps, oblique to the direction of tectonic transport, along the eastern edge of the Sulaiman fold belt (SFB). Shortening along the Zindapir anticlinorium reflects a fraction of 37 mm/yr convergence along thrust faults of flat-and-ramp geometry. The Zindapir anticlinorium serves an example for better understanding of oblique mountain fronts, active tectonics, and hydrocarbon exploration in the region. Highlights: Zindapir Anticlinorium (Pakistan) shows thin-skinned tectonics. Major deformation is accommodated by the passive roof duplex geometry. Basal decollement is situated in Permo-Triassic strata at a depth of 10 km. Cretaceous and younger strata uplifted 2–4 km above regional stratigraphic level.